Exploration of senescence-associated genes by differential display reverse transcription polymerase chain reaction: Prosaposin as a novel senescence-associated gene - Kim, Nam-Yi; Woo, Anh-Myung; Kim, Jae-Ryong; Lee, ChuHee (Archives of pharmacal research, 2009)
To understand the process and molecular mechanism of cellular aging, we explored novel senescence-associated genes using rat tissues with different age. Using total RNAs from 6 and 24-month old rat tissues, differential display reverse transcriptase polymerase chain reaction (DD RT-PCR) were performed and 12 differentially expressed genes (DEGs) which were down- or up-regulated in aged rat tissues were found. Among these DEGs, the level of prosaposin mRNA was elevated of in senescent human dermal fibroblast (HDF) and human umbilical vein endothelial cells (HUVECs). It was further confirmed that expression of prosaposin was up-regulated in prematurely senescent HUVECs induced by hydrogen peroxide or interferon-γ treatment. Taken together, we report the up-regulation of prosaposin in the senescent HDF and HUVECs as well as in hydrogen peroxide or interferon-γ induced prematurely senescent HUVECs, suggesting that prosaposin might be a novel senescence-associated gene.